Clinical efficacy and economic evaluation of online cognitive behavioral therapy for major depressive disorder: a systematic review and meta-analysis. (2nd January 2018) - Ahern, Elayne; Kinsella, Stephen; Semkovska, Maria
ABSTRACT: Introduction : Leading cause of disability worldwide, depression is the most prevalent mental disorder with growing societal costs. As mental health services demand often outweighs provision, accessible treatment options are needed. Our systematic review and meta-analysis evaluated the clinical efficacy and economic evidence for the use of online cognitive behavioral therapy (oCBT) as an accessible treatment solution for depression. Areas covered : Electronic databases were searched for controlled trials published between 2006 and 2016. Of the reviewed 3, 324 studies, 29 met the criteria for inclusion in the efficacy meta-analysis. The systematic review identified five oCBT economic evaluations. Therapist-supported oCBT was equivalent to face-to-face CBT at improving depressive symptoms and superior to treatment-as-usual, waitlist control, and attention control. Depression severity, number of sessions, or support did not affect efficacy. From a healthcare provider perspective, oCBT tended to show greater costs with greater benefits in the short term, relative to comparator treatments. Expert commentary : Although efficacious, further economic evidence is required to support the provision of oCBT as a cost-effective treatment for depression. Economic evaluations that incorporate a societal perspective will better account for direct and indirect treatment costs. Nevertheless, oCBT shows promise of effectively improving depressive symptoms, considering limited mental healthcare resources.